Immune-related adverse events associated with PD-1 and PD-L1 inhibitors for nonsmall cell lung cancer: Protocol for a systematic review and meta-analysis. Issue 44 (November 2017) - Sun, Xiaoying; Roudi, Raheleh; Chen, Shangya; Fan, Bin; Li, Hong Jin; Zhou, Min; Li, Xin; Li, Bin
Abstract: Introduction: Nonsmall cell lung cancer accounts for approximately 80% of all lung cancers, and approximately 75% of cases are diagnosed in the middle and late stages of disease. Unfortunately, limited treatment does not improve the prognosis of advanced disease. Monoclonal antibodies targeting programmed cell death protein-1 (PD-1) and programmed death-ligand 1 (PD-L1) represent a new treatment paradigm for nonsmall cell lung cancer. Nevertheless, the immune-related adverse events (irAEs) associated with PD-1 and PD-L1 inhibitors are unique, and early recognition and treatment of these events are essential. Methods and Analysis: A systematic literature search will be performed using the EMBASE, MEDLINE, and Cochrane databases to identify relevant articles published in any language. Randomized clinical trials, case series, and case reports of PD-1 and PD-L1 inhibitors in the treatment of nonsmall cell lung cancer will be included. All meta-analyses will be performed using RevMan software. The quality of the studies will be evaluated using the guidelines listed in the Cochrane Handbook. If the necessary data are available, then subgroup analyses will be performed for high-, median-, and low-dose cohorts. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses statements will be followed until the findings of the systematic review and meta-analysis are reported. Conclusions: This will be the first systematic review and meta-analysis to describe previously reported irAEs related to PD-1 and PD-L1 inhibitors in the treatment of nonsmall cell lung cancer.